The Impact of Socioeconomic Factors on Educational Management: Comparative Analysis of International Policies and Practices - Cardona, Louisse Scarrlet (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2024)
This study investigates the influence of socioeconomic factors on educational management through a comparative analysis of international policies and practices. Utilizing qualitative methods, including literature review and library research, the study examines the correlation between socioeconomic status and educational outcomes across diverse contexts. The analysis encompasses various dimensions of educational management, including resource allocation, curriculum development, teacher training, and student support systems. By exploring the policies and practices implemented in different countries, the study aims to identify common trends and unique approaches in addressing the impact of socioeconomic factors on educational management. Findings reveal that socioeconomic disparities significantly affect educational opportunities and outcomes, influencing access to quality education, student performance, and educational equity. Moreover, the study highlights the importance of tailored interventions and policy reforms to mitigate the negative effects of socioeconomic factors on educational management. The comparative analysis underscores the need for context-specific strategies that consider the socioeconomic landscape, cultural norms, and institutional capacities of each country. The study concludes by advocating for collaborative efforts among policymakers, educators, and stakeholders to develop inclusive educational policies and practices that foster equitable learning environments and enhance educational outcomes for all students.